2004
DOI: 10.1016/s0092-8674(03)01036-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for FEN-1 Substrate Specificity and PCNA-Mediated Activation in DNA Replication and Repair

Abstract: Flap EndoNuclease-1 (FEN-1) and the processivity factor proliferating cell nuclear antigen (PCNA) are central to DNA replication and repair. To clarify the molecular basis of FEN-1 specificity and PCNA activation, we report here structures of FEN-1:DNA and PCNA:FEN-1-peptide complexes, along with fluorescence resonance energy transfer (FRET) and mutational results. FEN-1 binds the unpaired 3' DNA end (3' flap), opens and kinks the DNA, and promotes conformational closing of a flexible helical clamp to facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
368
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 266 publications
(389 citation statements)
references
References 50 publications
18
368
2
1
Order By: Relevance
“…7B nonetheless show that the DNA is bent in the Taq polymerase-DNA complex, forming an angle of about 120°presumably at the junction between the upstream duplex and downstream duplex. Such upstream and downstream duplexes bending was also observed in P. furiousus flap endonuclease I interactions with DNA substrates by molecular modeling (41), and in the crystal structure of Archaeoglobus fulgidus flap endonuclease I in complex with a similar overlap flap DNA substrate (42). DISCUSSION Our SANS results suggest that, when Taq polymerase binds the overlap flap DNA substrate, tethered Klentaq and 5Ј-nuclease domains and their accompanying active sites do not approach closely enough to allow the simultaneous upstream primer extension and downstream primer cleavage, as speculated, to generate a ligatable nick.…”
Section: Resultsmentioning
confidence: 61%
“…7B nonetheless show that the DNA is bent in the Taq polymerase-DNA complex, forming an angle of about 120°presumably at the junction between the upstream duplex and downstream duplex. Such upstream and downstream duplexes bending was also observed in P. furiousus flap endonuclease I interactions with DNA substrates by molecular modeling (41), and in the crystal structure of Archaeoglobus fulgidus flap endonuclease I in complex with a similar overlap flap DNA substrate (42). DISCUSSION Our SANS results suggest that, when Taq polymerase binds the overlap flap DNA substrate, tethered Klentaq and 5Ј-nuclease domains and their accompanying active sites do not approach closely enough to allow the simultaneous upstream primer extension and downstream primer cleavage, as speculated, to generate a ligatable nick.…”
Section: Resultsmentioning
confidence: 61%
“…In elegant genetic studies, Wu et al (16) provided evidence that the DNA structure endonuclease FEN-1(Rad27) is involved in nucleolytic processing events that occur after end alignment in NHEJ. The participation of FEN-1(Rad27), a multifunctional enzyme, in DNA replication and the long patch subpathway of base excision repair is mediated by an interaction with proliferating cell nuclear antigen (13,17,(21)(22)(23). In this study, we identified and characterized physical and functional interactions between FEN-1(Rad27) and both Pol4 and Dnl4/Lif1, the enzymes that catalyze the gap-filling and ligation steps of NHEJ, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…FEN-1 is member of the growing family of proteins that bind to the interdomain connector loop of proliferating cell nuclear antigen, which functions as a ring-shaped homotrimer (17)(18)(19)(20). This interaction with proliferating cell nuclear antigen, which involves residues in addition to the conserved proliferating cell nuclear antigen binding motif, stimulates the DNA structurespecific endonuclease activity of FEN-1 and presumably contributes to the participation of FEN-1 in Okazaki fragment maturation and long patch base excision repair (13,17,(21)(22)(23). Although genetic studies in yeast indicate that FEN-1(Rad27) is involved in the processing of aligned NHEJ intermediates with 5Ј flaps (16,24), the protein-protein interactions that specifically recruit FEN-1 to the NHEJ intermediates have not been identified.…”
mentioning
confidence: 99%
“…PCNA is a highly conserved eukaryotic homotrimeric protein that assembles around DNA to form a sliding clamp and acts as a processivity factor for the replicative polymerase (reviewed in [16]). PCNA interacts with a large variety of proteins involved in DNA replication, lesion bypass, DNA repair, and cell cycle control, such as DNA polymerases δ and ε [17], DNA polymerase η [18], LIGI [19], MSH3 and MSH6 [20], FEN1 [21], GADD45 [22], and p21 [23]. An eight amino acid conserved motif (Q-x-x-[I/L/M]-x-x-F-[F/ Y]) in these proteins modulates their binding to PCNA [24].…”
Section: Introductionmentioning
confidence: 99%